Research progress in calculating net community production of marine ecosystem by remote sensing - Wang, Yingqi; Wang, Kui; Bai, Yan; Wu, Di; Zheng, Hao (Frontiers in Marine Science, 2023)
Net community production (NCP) is defined as the difference between gross primary production (GPP) and total community respiration (R). NCP indicates the balance between the production and consumption of community organic carbon, therefore making it a key parameter for evaluating the efficiency of carbon sequestration using the biological pump (BP). It is difficult to quantify NCP directly via satellite, because there are complex processes in community production and respiration. We reviewed previous research on satellite-based NCP and classified the methods into two primary categories: empirical methods and semi-analytical methods. The former category was established based on numerical relationships between NCP and satellite-based proxies, while the latter was developed by utilizing mechanistic analysis to establish quantitative expressions linking NCP to such proxies. Although satellite-based calculations of NCP have been attempted, they still suffer from significant uncertainties. Future research should focus on the precise calculation of satellite-based NCP by investigating the underlying processes and mechanisms that regulate NCP, developing regional models, and increasing the resolution of satellite sensors, as well as applying satellite lidar and coordinated multi-sensor observation technology.